Enhancing Maritime Security: Challenges and Strategies in Indonesia's Natuna Sea - Marliani Marliani (Journal of Maritime Policy Science, 2024)
The Natuna Sea, a strategic region within Indonesia's exclusive economic zone, faces multifaceted maritime security challenges that threaten national sovereignty, economic interests, and regional stability. This abstract explores the key issues and strategic responses to enhance maritime security in this vital area. Indonesia's maritime security challenges in the Natuna Sea are driven by illegal, unreported, and unregulated (IUU) fishing, territorial disputes, and transnational crimes such as smuggling and human trafficking. The encroachment of foreign fishing vessels, particularly from neighboring countries, exacerbates the IUU fishing problem, undermining local economies and depleting fish stocks. Additionally, overlapping territorial claims, particularly with China, complicate Indonesia's efforts to assert its sovereignty and maintain peace in the region. To address these challenges, Indonesia has developed a comprehensive maritime security strategy that includes diplomatic, legal, and operational measures. Diplomatic efforts focus on strengthening regional cooperation through ASEAN and other multilateral forums to foster dialogue and build consensus on maritime security issues. Legal measures involve the enforcement of national and international laws, including the United Nations Convention on the Law of the Sea (UNCLOS), to uphold Indonesia's territorial rights and combat IUU fishing. Operationally, Indonesia has enhanced its maritime patrols, surveillance capabilities, and naval presence in the Natuna Sea. The establishment of the Maritime Security Agency (Bakamla) and the deployment of advanced technology, such as unmanned aerial vehicles (UAVs) and satellite monitoring, have improved the detection and interdiction of illegal activities. Despite these efforts, challenges persist due to resource constraints, coordination issues among agencies, and the complex geopolitical landscape. This abstract underscores the importance of a holistic and adaptive approach to maritime security, integrating diplomatic, legal, and operational strategies.